2014
DOI: 10.1103/physrevx.4.031031
|View full text |Cite
|
Sign up to set email alerts
|

Light Guiding by Effective Gauge Field for Photons

Abstract: We propose a waveguiding mechanism based on the effective gauge potential for photons. The waveguide geometry consists of core and cladding regions with the same underlying dispersion relation, but subject to different gauge potentials. This geometry can be realized in a dynamically modulated resonator lattice and provides a conceptually straightforward and dynamically reconfigurable mechanism for generating a one-way waveguide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
106
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 26 publications
0
106
0
Order By: Relevance
“…The concept is based on imparting a suitable form of momentum biasing that breaks time-reversal symmetry, achieved with mechanical motion or with spatiotemporal modulation (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In this paper, for the first time to our knowledge, we apply these concepts to emitting/absorbing systems, showing that it is possible to realize magnetic-free nonreciprocal structures that can emit without absorbing from the same direction over a broad frequency range.…”
mentioning
confidence: 99%
“…The concept is based on imparting a suitable form of momentum biasing that breaks time-reversal symmetry, achieved with mechanical motion or with spatiotemporal modulation (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In this paper, for the first time to our knowledge, we apply these concepts to emitting/absorbing systems, showing that it is possible to realize magnetic-free nonreciprocal structures that can emit without absorbing from the same direction over a broad frequency range.…”
mentioning
confidence: 99%
“…A spatially varying profile of this shifting introduces a pseudomagnetic field that bends light in real space, in a similar fashion to a magnetic field bending electron motion. Such a mechanism in bending light has a very different nature to the usual light bending from an index gradient, leading to a series of unconventional optical phenomena, including one-way photonic edge states, photonic Landau levels, and alternative ways to achieve negative refraction and waveguiding [13][14][15][16][17][18][19][20][21][22][23]. Apart from various existing schemes for realizing such a pseudomagnetic field through the introduction of either spatial or temporal asymmetry into the mutual coupling within an array of resonators, it has been recently shown that such a pseudomagnetic field can be captured simply in terms of effective medium parameters, which can then be realized using metamaterials [24].…”
Section: Introductionmentioning
confidence: 99%
“…A results in a new system as described by a dispersion relation ω(k − A) 17,40 . For the system above, by applying a change of the gauge potential:…”
mentioning
confidence: 99%